Cosmic electrodynamics : electrodynamics and magnetic hydrodynamics of cosmic plasmas - Fleishman, Gregory D. (Astrophysics and Space Science Library, 2013)
This volume offers a deep and detailed overview of plasma behavior in diverse astrophysical conditions. The presentation is based on a solid science foundation that includes well established physical laws of electromagnetism, hydrodynamics, classical and quantum mechanics and other relevant fields of science. Qualitative ideas and descriptions are followed by quantitative derivations and estimates of key physical quantities, and the results of theories and models are confronted with modern observational data obtained from numerous international science programs. Fundamental astrophysical phenomena, such as charged particle acceleration and magnetic field generation, are presented along with spectacular phenomena, such as stellar winds (including ultra-relativistic pulsar wind), supernova explosions and evolution of its remnants, and solar flares.